Techno-economic analysis of combining forward osmosis-reverse osmosis and anaerobic membrane bioreactor technologies for municipal wastewater treatment and water production. (February 2020) - Vinardell, Sergi; Astals, Sergi; Mata-Alvarez, Joan; Dosta, Joan
Highlights: The combination of FO, RO and AnMBR for sewage treatment was analysed. The minimum treatment cost of FO-RO + AnMBR system was estimated at 0.81 € m −3 . The minimum water production cost of FO-RO was estimated at 0.80 € m −3 . FO recovery was the main driver of CAPEX and OPEX. FO membrane fluxes of 10 LMH would make the FO-RO + AnMBR system more attractive. Abstract: The economic feasibility of combining forward osmosis (FO), reverse osmosis (RO) and anaerobic membrane bioreactor (AnMBR) technologies for municipal wastewater treatment with energy and water production was analysed. FO was used to pre-concentrate the AnMBR influent, RO for draw solution regeneration and water production, and AnMBR for wastewater treatment and energy production. The minimum wastewater treatment cost was estimated at 0.81 € m −3, achieved when limiting the FO recovery to 50% in a closed-loop scheme. However, the cost increased to 1.01 and 1.27 € m −3 for FO recoveries of 80% and 90%, respectively. The fresh water production cost was estimated at 0.80 and 1.16 € m −3 for an open-loop scheme maximising water production and a closed-loop scheme, respectively. The low FO membrane fluxes were identified as a limiting factor and a sensitivity analysis revealed that FO membrane fluxes of 10 LMH would significantly improve the competitiveness of FO-RO + AnMBR technology.